Reading James Missiologically : the missionary motive, message, and methods of james - Urga, Abeneazer G.; Udall, Jessica A.; Smither, Edward L. (Littleton : William Carey Publishing, 2025)
"What can James teach us about mission? While books on a New Testament theology of mission abound, most of them focus only on certain tried-and-true books and passages while often ignoring the contribution of the General Epistles. In Reading Hebrews Missiologically and Reading 1 Peter Missiologically, we began to address this gap in missiological scholarship, and we seek to continue in the same vein in this work on the book of James. Reading James Missiologically explores the missionary dimensions of the Epistle of James through three parts: the missionary motive is the reason behind missionary efforts (the why), the missionary message reveals what missionaries communicate (the what), and the missionary methods outline strategies for mission (the how). The global contributors examine James's profound call to action among the poor and inspire believers toward holistic engagement with the world as "doers of the word, not hearers only" (Jas 1:22 ESV)"--